Borane‐Induced Dimerization of Arylallenes. Issue 42 (28th September 2018) - Tao, Xin; Daniliuc, Constantin G.; Dittrich, Dustin; Kehr, Gerald; Erker, Gerhard
Abstract: A series of arylallenes react with HB(C6 F5 )2 in a 2:1 molar ratio to give the tail‐to‐tail 1, 6‐diaryl‐2‐boryl‐hexa‐1, 5‐diene coupling products. The reaction of the phenylallene substrate with HB(C6 F5 )2 was shown to initially give the 2‐boryl‐3, 4‐diphenyl‐1, 5‐hexadiene head‐to‐head coupling product which then rearranged, by a thermally induced Cope rearrangement, into the final product. Abstract : Heads or tails? Monoalkylallenes are catalytically cyclotrimerized by HB(C6 F5 )2, whereas arylallenes react with HB(C6 F5 )2 to give 1, 6‐diaryl‐2‐boryl‐hexa‐1, 5‐diene tail‐to‐tail coupling products. The reaction of phenylallene with HB(C6 F5 )2 initially gives the 2‐boryl‐3, 4‐diphenyl‐1, 5‐hexadiene head‐to‐head coupling product, which then rearranges, by a thermally induced Cope rearrangement, into the final product.